Teaching information literacy reframed 50+ framework-based exercises for creating information-literate learners - Burkhardt, Joanna M. (Neal-Schuman, an imprint of the American Library Association, 2016)
The six threshold concepts outlined in the Framework for Information Literacy for Higher Education are not simply a revision of ACRL's previous Information Literacy Competency Standards for Higher Education. They are instead an altogether new way of looking at information literacy. In this book, instructional librarian Burkhardt decodes the Framework, putting its conceptual approach into straightforward language while offering more than 50 classroom-ready Framework-based exercises. Guiding instructors towards helping students cross each threshold, this book discusses the history of the development of the Framework document and briefly deconstructs the six threshold concepts; addresses each threshold concept, scaffolding from the beginner level to the intermediate level; includes exercises that can be used in the one-shot timeframe as well as others designed for longer class sessions and semester-long courses; offers best practices in creating learning outcomes, assessments, rubrics, and teaching tricks and tips; and looks at how learning, memory, and transfer of learning applies to the teaching of information literacy.